2014
DOI: 10.1155/2014/297431
|View full text |Cite
|
Sign up to set email alerts
|

Technology Efficacy in Active Prosthetic Knees for Transfemoral Amputees: A Quantitative Evaluation

Abstract: Several studies have presented technological ensembles of active knee systems for transfemoral prosthesis. Other studies have examined the amputees' gait performance while wearing a specific active prosthesis. This paper combined both insights, that is, a technical examination of the components used, with an evaluation of how these improved the gait of respective users. This study aims to offer a quantitative understanding of the potential enhancement derived from strategic integration of core elements in deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The micrograph of M0 detected the formation of the cement particles that showed the growth of rods of ettringite phase (C 3 A. 3CaSO 4 . 32H 2 O).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The micrograph of M0 detected the formation of the cement particles that showed the growth of rods of ettringite phase (C 3 A. 3CaSO 4 . 32H 2 O).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Chandra et al, [36] reported that the retardation effects of in cement/cement admixtures due to the interaction of Ca 2+ ions with chemical admixtures, which holds their action and causes the acceleration of early ettringite gel formation or inhibition of the conversion of ettringite to monosulphate (C 3 A. 3CaSO 4 . 12H 2 O).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in prosthetic knee systems are of increasing importance to assist transfemoral amputees perform their different daily activities [ 1 ] such as walking, stair climbing, and running [ 2 , 3 ] more naturally. Prosthetic knee devices are categorized into passive and active types [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the effect of different prosthetic components [6][7][8] and of amputation level [9][10][11][12][13][14] during amputee gait have led to consistent findings of reduced peak ankle plantar-flexion moment and power and increased peak hip power generation and absorption in amputees. This has led to several avenues of research, particularly the design and development of active (powered) prosthetic limbs [15][16][17]. However, given the majority of amputees use passive prosthetic limbs, understanding how these devices interact with the body during locomotion should remain a priority and may lead to improved passive devices with better energy storage and return characteristics, perhaps utilising intelligent control.…”
mentioning
confidence: 99%